Demographic change: Ecological and polycentric challenges for white Christianity in urban South Africa - Resane, Kelebogile T. (HTS teologiese studies, 2019)
This article demonstrates how white Christianity in urban South Africa is fated by demographic change. The repeal of apartheid in 1994 enacted some sociocultural changes in urban South Africa. The white population exited the city and town centres, followed by the black South Africans. The historical relationship of the government under the National Party (NP) and the Dutch Reformed Church (DRC) led to latters’ redundancy in the cities. The cultural development towards multiculturalism led to polycentric focus where the suburban peripheries and the city centres experience some form of socio- and cultural-economic developments. Two proposals are made to redress the situation. Firstly, a rethinking was suggested of the theology of the city, which should always demonstrate solidarity with the poor and the marginalised trapped within the decadent city culture. Secondly, a missiological refocus was suggested, which should pursue, embrace and include activities that are not paternalistic.